Characterization of Sago Starch-Based Biofoam with Corn Husk Fiber Filler - Rozanna Dewi; Novi Sylvia; Zulnazri; Retnowulan, Sri Rahayu; Muarif, Agam; Fikri, Ahmad; Medyan Riza (Jurnal Bahan Alam Terbarukan, 2024)
The use of biofoam is one of the ways to reduce plastic waste that pollutes the environment. In this research, we want to develop biofoam from sago starch as a basic ingredient with the addition of corn husk fiber filler and the addition of magnesium stearate which aims to improve mechanical characteristics, thermal, morphological, water absorption and biodegradabillity. Variations of corn husk fiber used were 45 g, 50 g, 55 g and 60 g, with variations in the concentration of NaOH solvent used for cellulose extraction were 3%, 5%, 7% and 9%. The mechanical characteristics (tensile strength) of the resulting biofoam range from 1.37 – 2.45 MPa. The chemical bonding of biofoam was seen through Fourier Transform Infrared Spectroscopy (FTIR) and showed that biofoam is hydrophilic which binds to water so that it is easily degraded by soil. Thermal characteristics were tested through Differential Scanning Calorimetry (DSC) and showed a melting point of 410.68oC at 45 g of fiber and 5% NaOH and a melting point of 410.86oC at 55 g fiber and 5% NaOH. Thermal stability was analyzed through Thermal Gravimetry Analysis (TGA) and the most thermally stable biofoam was biofoam with 45 g of corn husk fiber and 5% NaOH. The surface morphology test using a Scanning Electron Microscope (SEM) showed that the morphological structure of the corn husk fiber biofoam was uneven and there were bubbles on the surface of the biofoam. The water absorption test shows results between 5.72 – 14.43%. The lowest density test for biofoam is using 55 g fiber weight and 3% NaOH concentration, while the highest density is 60 g fiber weight and 9% NaOH concentration. The results of the biodegradability test showed that the biofoam decomposes completely within 40-45 days, the soil moisture factor greatly affects the rate of biodegradability.